1991
DOI: 10.1093/nar/19.19.5139
|View full text |Cite
|
Sign up to set email alerts
|

Activation of restriction endonucleaseEcoRII does not depend on the cleavage of stimulator DNA

Abstract: The restriction endonuclease EcoRII is unable to cleave DNA molecules when recognition sites are very far apart. The enzyme, however can be activated in the presence of DNA molecules with a high frequency of EcoRII sites or by oligonucleotides containing recognition sites: Addition of the activator molecules stimulates cleavage of the refractory substrate. We now show that endonucleolysis of the stimulator molecules is not a necessary prerequisite of enzyme activation. A total EcoRII digest of pBR322 DNA or ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…It has been shown that all endonucleases requiring two sites for catalysis cleave plasmid substrates with a single site less efficiently than those with two sites. The cleavage efficiency of solitary sites, however, may be increased by providing a second site on a short oligonucleotide duplex in trans (22,27,42). SgrAI did not follow this pattern, because the canonical sites provided on oligonucleotide duplexes inhibited the cleavage of a plasmid substrate containing a single canonical site (34).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been shown that all endonucleases requiring two sites for catalysis cleave plasmid substrates with a single site less efficiently than those with two sites. The cleavage efficiency of solitary sites, however, may be increased by providing a second site on a short oligonucleotide duplex in trans (22,27,42). SgrAI did not follow this pattern, because the canonical sites provided on oligonucleotide duplexes inhibited the cleavage of a plasmid substrate containing a single canonical site (34).…”
Section: Discussionmentioning
confidence: 98%
“…In an EcoRII complex that is bound to two copies of its recognition sequence, only one sequence is cleaved, whereas the other sequence serves as an allosteric activator (23, 24, 26 -28). The products of the EcoRII reaction (cleaved sites) may also serve as an allosteric activator by stimulating the cleavage activity of EcoRII at the refractory sites (27). In this respect, SgrAI resembles EcoRII, because it also can use the reaction products to assist in cleavage at other sites; however, there is a major difference between the two enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme has a unique ability to search for the presence of two substrate sites before cleavage. The activation of enzyme occurs when an EcoRII dimer interacts with two DNA-recognition sites (Kru È ger et al, 1988;Pein et al, 1991;Gabbara & Bhagwat, 1992;Petrauskene et al, 1994).…”
Section: Introductionmentioning
confidence: 99%